Polanyi, political-economic opportunity structure and protest: capitalism and contention in the post-communist Czech Republic - Císař, Ondřej; Navrátil, Jiří (Social Movement Studies, 2016)
Drawing on Polanyian logic, we focus on the gradual institutionalization of capitalism in the Czech Republic and the protests accompanying this process. We hypothesize that different configurations of political economy, or what we term the political economic opportunity structure, trigger different popular responses and are a potent indicator of expected protest forms. To analyze this we chose to carry out a country case study, in which many variables commonly associated with political mobilization, in particular the state’s institutional structure, are kept constant. By contrast, models of political economy vary over time, as a function of the extent and form of the international integration of capitalism. We focus on three configurations of political economy – national, globalized and austerity models – and for each one, identify the characteristics and mechanisms, i.e. concrete policy measures, that shape particular protest patterns in the context of our case study. In theoretical terms, this paper seeks to present one possible response, in this case a Polanyian response, to recent complaints about the disappearance of capitalism from social movement studies. At the same time, given the focus of this special issue, our goal is to analyze the current wave of anti-austerity protest that emerged in relation to what has been labelled the Great Recession.
Keywords: Czech Republic; anti-austerity; economic protest; political economic opportunity structure; political opportunity structure; social movement studies